Penambahan Omzet Usaha Jasa Penjahit Kebaya - Luh Putu Safitri Pratiwi; Ni Putu Nanik Hendayanti; I Ketut Putu Suniantara (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Good marketing is one of the important things in the development and addition of income in entrepreneurship. The problem faced in the business of sewing clothes is that partners are not too focused on marketing management. Partners rely more on conventional marketing systems, even though the new location of the partner services business is not too strategic. This causes the field of business is difficult to be recognized by the wider community so that it becomes an obstacle in developing its business. The purpose of this activity is to provide solutions to the problems being faced, namely by implementing marketing management using Facebook pages. With the socialization and marketing management training, it is expected to be able to add insight into the actors in utilizing the internet as an online promotion media to introduce their business fields to the wider community in increasing their business income. The result of this activity was that the Partners were very enthusiastic, both from socialization to evaluation. Assistance with the use of the Facebook pages application is expected to continue to be used in a sustainable manner